2004
DOI: 10.1111/j.1365-2672.2004.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acanthamoeba polyphaga surface carbohydrate exposure by FITC-lectin binding and fluorescence evaluation

Abstract: Aims: Characterization of the representative protozoan Acanthamoeba polyphaga surface carbohydrate exposure by a novel combination of flow cytometry and ligand-receptor analysis. Methods and Results: Trophozoite and cyst morphological forms were exposed to a panel of FITC-lectins. Population fluorescence associated with FITC-lectin binding to acanthamoebal surface moieties was ascertained by flow cytometry. Increasing concentrations of representative FITC-lectins, saturation binding and determination of K d an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…For this purpose, we turned our attention to the surface glycans that had already been described in Acanthamoeba: glucose, mannose, GalNAc, and GlcNAc (10). APMV particles were incubated in solutions with each of these glycans at a concentration of 10, 25, 50, 75, 100, or 125 g/ml, followed by incubation with A. castellanii cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, we turned our attention to the surface glycans that had already been described in Acanthamoeba: glucose, mannose, GalNAc, and GlcNAc (10). APMV particles were incubated in solutions with each of these glycans at a concentration of 10, 25, 50, 75, 100, or 125 g/ml, followed by incubation with A. castellanii cells.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the role of glycans in viral adhesion to distinct organisms, 10 6 TCID 50 of viruses (APMV, LAPMV, DAPMV, and mimivirus M4) treated with various concentrations of different carbohydrates (glucose, mannose, N-acetylglucosamine, N-acetylgalactosamine, chitin, and peptidoglycan) were incubated with the same amount of microorganism cells and mosquito legs using the same conditions described above. The results were plotted in a column graph, and the statistical significance was given by a two-tailed Student's t test, performed using GraphPad Prism software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major population of N-glycans detected in MCF-7 and MCF/ADR cells corresponded to high-mannose structures, and some high mannoses in particular peak 2, 8, 17 were dramatically increased in drug-resistant MCF/ADR cell line. Moreover, MCF/ADR cells showed a significant increase of fucosylated and sialylated oligosaccharides (peak 3,5,10,12,16,20,22). Therefore, monitoring of the N-glycan profile would be an important step in the prevention of tumor MDR and would increase our understanding of resistance mechanisms.…”
Section: Figmentioning
confidence: 99%
“…Although there are various earlier reports on a partial characterization of lipophosphonoglycan (10) and the presence of a N-acetylglucosaminyl-1-phosphotransferase (11) as well as various radiolabeling (12), lectin binding (12)(13)(14)(15) or monosaccharide composition studies (16), our present data are the first regarding the actual structures of glycosylated macromolecules of this genus. As it has been shown that many protozoal parasites synthesize highly unique N-glycans (17), it can be hypothesized that the investigation of the N-glycosylation of parasitic and nonparasitic Acanthamoeba strains may yield insights into virulence factors.…”
mentioning
confidence: 77%